2017
DOI: 10.1002/2017gl072850
|View full text |Cite
|
Sign up to set email alerts
|

Direction‐finding measurements of Jovian low‐frequency radio components by Juno near Perijove 1

Abstract: With the aid of the radio and plasma wave (Waves) instrument on board the Juno spacecraft, the first scientific close encounter to Jupiter (Perijove 1) of Juno led to an opportunity to perform direction‐finding measurements of the intense Jovian broadband kilometric (bKOM) radiation at 10 to 142 kHz, two escaping continuum radiation (ECR) events at 9 to 22 kHz, and two narrowband kilometric (nKOM) radiation events at 45–112 kHz. We conclude that the northern bKOM radio sources are localized on M‐shell = 50–60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 39 publications
6
28
0
Order By: Relevance
“…We presented simultaneous observations of auroras at radio and UV wavelengths as observed from Juno during PJ4 through PJ6 over both hemispheres of Jupiter. Using Jovian radio observations and UV aurora images taken at the same or similar times, we confirmed that bKOM radio sources are tied to the UV main oval, which was originally suggested by the Ulysses radio DF study (Ladreiter et al, ) and the initial Juno radio DF and in situ studies (Imai et al, , ; Kurth, Imai, Hospodarsky, Gurnett, Louarn, et al, ; Kurth, Imai, Hospodarsky, Gurnett, Tetrick, et al, ) but without concurrent UV aurora observations.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…We presented simultaneous observations of auroras at radio and UV wavelengths as observed from Juno during PJ4 through PJ6 over both hemispheres of Jupiter. Using Jovian radio observations and UV aurora images taken at the same or similar times, we confirmed that bKOM radio sources are tied to the UV main oval, which was originally suggested by the Ulysses radio DF study (Ladreiter et al, ) and the initial Juno radio DF and in situ studies (Imai et al, , ; Kurth, Imai, Hospodarsky, Gurnett, Louarn, et al, ; Kurth, Imai, Hospodarsky, Gurnett, Tetrick, et al, ) but without concurrent UV aurora observations.…”
Section: Discussionsupporting
confidence: 80%
“…The estimated magnetic M values from the Waves direct and DF methods yield 10 to 12 for the PJ4 north pass, significantly lower than for the PJ5 north event at M = 44–56 and PJ6 north event at M = 22–52 as shown in Table . These M values are within the estimates of the Ulysses bKOM DF study at M = 5–58 (Ladreiter et al, ), but only PJ5 and PJ6 events are in agreement with those of the initial Juno bKOM studies (Imai et al, , ; Kurth, Imai, Hospodarsky, Gurnett, Louarn, et al, ; Kurth, Imai, Hospodarsky, Gurnett, Tetrick, et al, ) at M = 50–60. Another possibility for the PJ4 north event is a response to transient diffusive injections toward the Io plasma torus (e.g., Louarn et al, ).…”
Section: Northern Bkom‐uv Aurorassupporting
confidence: 83%
See 2 more Smart Citations
“…Example VIP4 field lines with a disk current sheet [Connerney et al, 1981] are shown in blue. The low-latitude R-X cutoff incorporates a modified plasma sheet density model [Imai et al, 2017c]. The red dots indicate times when Juno passed through or close to auroral radio sources.…”
Section: Research Lettermentioning
confidence: 99%